Implementasi Model Pembelajaran Make A Match Dengan Pendekatan Contextual Teaching And Learning Untuk Meningkatkan Kemampuan Menulis Teks Berbentuk Procedure Pada Siswa Kelas XII MIPA 1 Man 1 Bungo - Karmi Karmi (Pusdikra Publishing, 2022)
This Classroom Action Research Aims to improve Students' Ability to write Texts in The Form Of Procedure. Based on the results of tests carried out by the author before conducting classroom action research and the results of observations during the teaching and learning process at MAN 1 Bungo, especially class XII IPA 1, most students have not been able to write text in the form of procedures. Procedure text learning is contained in the curriculum standard at the unit level of education (KTSP) in class XII semester 1. By using the Make a Match learning model, it is expected that students' ability to write procedure texts will increase. The results of this classroom action research showed that students' ability to write procedure texts could increase. This lies in the actions that researchers perform in each cycle 1, namely cycle 1 and cycle 2. This PTK was carried out in class XII IPA 1 MAN 1 Bungo with 2 cycles. In each cycle planning, implementing actions, observing, and reflecting on data were carried out. The collected data is processed quantitatively. Thus it can be emphasized that the Make a Match learning model can be used as an alternative to improve students' ability to write procedure texts in class XII IPA 1 MAN 1 Bungo. The results of the actions of each cycle obtained an overview of the results of cycle 1. The success rate of students reached an average of 67.4 with good category abilities. In cycle 2 the success of students reached an average of 73.85 with good category ability.